Blockade of the action of nitric oxide in human septic shock increases systemic vascular resistance and has detrimental effects on pulmonary function after a short infusion of methylene blue - Weingartner,R. (1999)
To investigate the role of nitric oxide in human sepsis, ten patients with severe septic shock requiring vasoactive drug therapy and mechanical ventilation were enrolled in a prospective, open, non-randomized clinical trial to study the acute effects of methylene blue, an inhibitor of guanylate cyclase. Hemodynamic and metabolic variables were measured before and 20, 40, 60, and 120 min after the start of a 1-h intravenous infusion of 4 mg/kg of methylene blue. Methylene blue administration caused a progressive increase in mean arterial pressure (60 [55-70] to 70 [65-100] mmHg, median [25-75th percentiles]; P<0.05), systemic vascular resistance index (649 [479-1084] to 1066 [585-1356] dyne s-1 cm-5 m-2; P<0.05) and the left ventricular stroke work index (35 [27-47] to 38 [32-56] g m-1 m-2; P<0.05) from baseline to 60 min. The pulmonary vascular resistance index increased from 150 [83-207] to 186 [121-367] dyne s-1 cm-5 m-2 after 20 min (P<0.05). Mixed venous saturation decreased from 65 [56-76] to 63 [55-69]% (P<0.05) after 60 min. The PaO2/FiO2 ratio decreased from 168 [131-215] to 132 [109-156] mmHg (P<0.05) after 40 min. Arterial lactate concentration decreased from 5.1 ± 2.9 to 4.5 ± 2.1 mmol/l, mean ± SD (P<0.05) after 60 min. Heart rate, cardiac filling pressures, cardiac output, oxygen delivery and consumption did not change. Methylene blue administration was safe and no adverse effect was observed. In severe human septic shock, a short infusion of methylene blue increases systemic vascular resistance and may improve myocardial function. Although there was a reduction in blood lactate concentration, this was not explained by an improvement in tissue oxygenation, since overall oxygen availability did not change. However, there was a significant increase in pulmonary vascular tone and a deterioration in gas exchange. Further studies are needed to demonstrate if nitric oxide blockade with methylene blue can be safe for patients with septic shock and, particularly, if it has an effect on pulmonary function.